Analisis Peran Media Sosial Sebagai Media Promosi Agen Dalam Meningkatkan Pemahaman Berasuransi Syariah - Dewi, Aulia Chintya; Ahmad, Yusrizal; Tambusai, Atika (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2024)
This aims study to determine the role of social media as a promotional media agent in increasing understanding of sharia insurance with a case study on family takaful agents in Medan city. This study uses a qualitative method that is descriptive. Then the data collection techniques in this study used interviews, observations (observations) and questionnaires with the Likert scale method with a total of 12 customer respondents who commented on social media agents who were informants in this study. The results of this study indicate that utilizing the role of social media as a promotional medium helps agents to increase understanding of sharia insurance, especially for customers. In fact, based on the results of interviews, Medan city family takaful agents argued that social media not only helps in promotion to increase understanding of sharia insurance, but can also generate new customers. Then to be able to measure the understanding of sharia insurance for family takaful customers it is measured through a questionnaire with four indicators, namely first, consumer knowledge with the results of very understanding criteria of 58.3%, understanding criteria of 33.3% and criteria of sufficient understanding of 8.3%. Second, previous or past experience with the results of very understanding criteria of 58.3%, 33.3% understanding criteria and 8.3% sufficiently understanding criteria. Then the third is information in the category of sufficient understanding of 100%. And fourth, social/environmental with sufficient understanding criteria of 100%. Keywords: Social Media, Promotion, Agent, Family Takaful